2020
DOI: 10.1039/d0ta01698e
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative charging behavior of water droplet driven freestanding triboelectric nanogenerators toward hydrodynamic energy harvesting

Abstract: A maximum power density of 1.838 W m−2 is achieved and 30 LEDs can be lighted up by the cumulative water droplets driven freestanding triboelectric nanogenerator demonstrating the great potential for hydrodynamic energy harvesting from rain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 36 publications
1
69
1
Order By: Relevance
“…This charge, accordingly, induces an electric field, which affects the protein properties. Such an effect can be observed for both water (and aqueous solutions [34][35][36][37]) and non-aqueous liquids [6,38]. We also demonstrated that the properties of a protein in a solution are affected by the flow of water flow through a coiled pipe [8].…”
Section: Discussionmentioning
confidence: 56%
“…This charge, accordingly, induces an electric field, which affects the protein properties. Such an effect can be observed for both water (and aqueous solutions [34][35][36][37]) and non-aqueous liquids [6,38]. We also demonstrated that the properties of a protein in a solution are affected by the flow of water flow through a coiled pipe [8].…”
Section: Discussionmentioning
confidence: 56%
“…The observed effect of the water, flowing through the coiled silicone pipe, on the adsorbability of HRP is apparently explained by the electromagnetic nature of the flow-induced field. The induction of such an electromagnetic field obviously occurs owing to a triboelectric effect consisting of a generation of charge in the liquid, flowing along a polymeric surface [ 8 , 29 , 30 , 31 , 32 , 33 , 34 ]. The triboelectrically induced charges induce an electromagnetic field, which, in turn, affects the protein during the incubation of its solution near the coil.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been verified that the effective contact area between the water droplet and FEP film was changed in the dynamic dropping process in earlier research. [41] When the droplet recedes from the ITO electrode and gets closer to another ITO electrode, the water droplet shrinks and involves fewer positive charges due to the reduced effective contact area. Thus, the electrons flow to the opposite direction due to both the rolling process of the water droplet and the change in charge amount of the water droplet through spreading and shrinking, (Figure 2a-iii).…”
Section: Working Mechanism Of the Fhngmentioning
confidence: 99%
“…[27][28][29][30][31][32] The TENGs and PENGs can convert electro-static energy and mechanical impact energy of raindrops into electrical energy, respectively. [33][34][35][36][37][38][39][40][41] The rain-TENGs were developed in separate form to directly harvest electro-static energy of raindrops based on the contact-electrification on solid/liquid interfaces. On the other hand, the rain-PENGs were developed in separate form to harvest mechanical impact energy of raindrops based on the strain on the device after raindrop impaction.…”
Section: Introductionmentioning
confidence: 99%